Identification of microRNAs regulating Hlxb9 gene expression during the induction of insulin‐producing cells. (2nd March 2016) - Mu, Changzheng; Wang, Tao; Wang, Xiaomei; Tian, He; Liu, Yong
Abstract: Bone marrow mesenchymal stem cells (bMSCs) with the capacity of self‐ renewal and multilineage differentiation are promising sources for cell replacement therapy in diabetes. Here, we developed an effective method with activin A, conophylline, and nicotinamide to induce mouse bMSCs to differentiate into insulin‐producing cells (IPCs). The homeobox gene Hlxb9 (encoding HB9) is prominently expressed in adult human pancreas, which can also play a key role during the induction of IPCs. To find the microRNAs (miRNAs) regulating Hlxb9 gene expression, we respectively used miRanda and TargetScan to predict and got the intersection, miR‐200a and miR‐141, further identified by the Dual‐Luciferase assay. The results illustrated miR‐200a and miR‐141 could inhibit the expression of Hlxb9 by binding to its mRNA 3′UTR. Furthermore, the expression of miR‐200a and miR‐141 was almost reciprocal to that of Hlxb9. Overexpression of miR‐200a and miR‐141 downregulated the expression of pancreatic progenitor cell markers Hlxb9 and Pdx1. Therefore, miR‐200a and miR‐141 may directly or indirectly regulate the expression of pancreatic islet transcription factors to control the differentiation of IPCs.